MEKANISME PASAR PENDEKATAN RETROSFEKTIF EKONOMI ISLAM - Ahmad Zaky Muzakkir (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2020)
ABSRACTMarket is the most visited place by the public. The market in Islamic view of economy requires morality in all economic activities, in particular : fair and healthy competition, honesty, transparancy, and fairness. The concept of market mechanisms in Islam is built on principles, that is: Ridho each other, healthy competition, honesty, transparency, and justice. Islam has tightened its people’s pace in financial activities and businesses that promote economic and social well-being. This goal is to analyze the mechanisms of the market in Islam and understand the concept of the market based on islamic sharia. In addition to understanding the principles of the market, which are based on islamic sharia. The method used in writing this article is descriptive. The data collected is then analyzed by qualitative methods. In this study the authors conducted an analysis of the market systems in Islam. The concept of the islamic natural marketaffirms that the market must stand above the principle of free competition but not absolute, but freedom wrapped in sharia rules. The concept of market mecanisme in Islam is built on principles: ridho, healthy compotition, honesty, or openness and justice.